2020
DOI: 10.1039/d0ra07429b
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of highly active phosphatase-like fluorescent cerium-doped carbon dots for in situ monitoring the hydrolysis of phosphate diesters

Abstract: The hydrolytic cleavage of BNPP was catalyzed and monitored by the fluorescent CeCDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…Using bis(4-nitrophenyl)phosphate, the phosphatase-like activity of the Ce-doped carbon dots [157] was systematically investigated and the study showed that the fluorescent Cedoped carbon dots could promote the hydrolysis of a phosphate ester. Enzyme-mimicking nanomaterials can hydrolyze DNA, organophosphate, and their analogs for future gene editing and environmentally friendly treatment of pesticide residues.…”
Section: Phosphatase Mimicsmentioning
confidence: 99%
“…Using bis(4-nitrophenyl)phosphate, the phosphatase-like activity of the Ce-doped carbon dots [157] was systematically investigated and the study showed that the fluorescent Cedoped carbon dots could promote the hydrolysis of a phosphate ester. Enzyme-mimicking nanomaterials can hydrolyze DNA, organophosphate, and their analogs for future gene editing and environmentally friendly treatment of pesticide residues.…”
Section: Phosphatase Mimicsmentioning
confidence: 99%
“…To begin with, N-methylmorpholine abstracts protons from Ce-bound water (Ce-H 2 O) molecules in an alkaline (N-methylmorpholine buffer solution) environment, resulting in the formation of nucleophilic cerium hydroxide (Ce-OH) species. 57,58 In step 1, the oxygen atom (OvP-) of 4-NPP coordinates with the aqua-hydroxyl active species Ce metal centre as it contains vacant 4f orbitals to form an intermediate species, which is useful for converting an intermolecular reaction to an intramolecular reaction. Step 2 involves the attack of the phosphorous atom of the 4-NPP molecule by an intramolecular metal hydroxide, which aids the release of the 4-nitrophenolate ion from the surface of the Ce-MOF catalyst, which was monitored using UV-vis spectroscopy.…”
Section: Kinetic Studies Of the Hydrolysis Of 4-nppmentioning
confidence: 99%
“…In the rate-determining step, the surface Ce-bound water molecules and 4-NPP react with each other and 4-NP is released from the surface of the Ce-MOF catalyst (Fig. S15 †).To begin with, N-methylmorpholine abstracts protons from Ce-bound water (Ce-H 2 O) molecules in an alkaline (N-methylmorpholine buffer solution) environment, resulting in the formation of nucleophilic cerium hydroxide (Ce-OH) species 57,58. In step 1, the oxygen atom (OvP-) of 4-NPP coordinates with the aqua-hydroxyl active species Ce metal centre as it contains vacant 4f orbitals to form an intermediate species, which is useful for converting an intermolecular reaction to an intramolecular reaction.…”
mentioning
confidence: 99%
“…fabricated Ce‐doped carbon dots (CeCDs) via a one‐step hydrothermal carbonization and investigated its mimetic phosphatase activity for phosphate ester hydrolysis cleavage. [ 161 ] The CeCdS exhibited good catalytic activity for promoting hydrolysis of bis(4‐nitrophenyl) phosphate (BNPP) and could also mimic phosphatase based on the Inner Filter Effect (IFE). Besides, there have been carbon‐based materials developed as SOD mimics for addressing the limitations of natural SOD.…”
Section: The Application Of Sustainable Carbon Materials In Catalysismentioning
confidence: 99%